Holistic development and wellbeing based on maqasid al-shari'ah : the case of south kalimantan, Indonesia - Abdullah Yusof, Selamah; Budiman, Mochammad Arif; Mohd Amin, Ruzita; Abideen, Adewale Abideen (Statistical Economic and Social Research and Training Centre for Islamic Countries, 2019)
Development in the true sense of the word should mean the betterment in all and everything of human life. This is consistent with Islam where development is seen as the enhancement of human wellbeing in both the material-physical and spiritual-religious-ethical dimensions and the establishment of social justice. The Maqasid al-Shari‘ah or the higher purposes of the Shari‘ah, provides a potentially comprehensive framework that can be used to measure the holistic multi-dimensional nature of development from an Islamic perspective. This study uses this framework based on its five components, namely, preservations of religion, life, intellect, posterity and wealth, in constructing an innovative index to measure the level of holistic development or wellbeing at the individual level. The sample consists of 418 randomly selected Muslims respondents living in South Kalimantan, Indonesia. The results show that South Kalimantan's level of holistic development is satisfactory and education plays a significant factor in holistic development, where it increases wellbeing in all aspects – intellect, life, posterity, wealth and religion. Men lag behind women in terms of development, while a stable and happy marriage impacts positively on the overall wellbeing. Thus, relevant policy recommendations related to education and the promotion of the institution of marriage must be emphasized to attain holistic development.